Evaluation of Impact on Public Transportation Headwinds: The Case of eThekwini Municipality Department of Transport - Ngwenya, Charles Tony Simphiwe; Dube, Nkosinathi (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2025)
The challenges and constraints confronting public transportation efficiency within the regulatory local government stewardship in the municipality’s spheres continue to have an inventory of misdemeanours such as mismanagement, dilapidating built environment in infrastructure, subdued digitalisation integration and transformation, contestation from privately owned transport entities, and poor control over transport operations. The public transport operations and its associated assets or infrastructure provide accessibility and act as wheels of economic growth and prosperity. These deliver a critical component of the envisaged good quality of life and standard of living from both the business perspectives and citizenry livelihoods state of affairs. The study investigated the public transport ecosystem and risks with associated resources. A structured questionnaire was used to collect data from pertinent stakeholders’ respondents to predict and explain insights and trends from both primary and secondary stakeholders within the public transport fraternity in the city. The positivist philosophical approach of the quantitative methodology, with its deductive paradigmatic stance, is selected in the study. The main findings indicate the lack of comprehensive consultation and buy-in within the broader stakeholder involvement. The findings further signified a gap in risk mitigation and resource optimisation and the significance of public service accessibility as a priority for policy-makers and practitioners. Findings indicate that the Transport Division realised the need to inculcate pragmatic execution in investing resources and capabilities from a problem-solving and decision-making perspective. This could yield sustained public service deliverables in desirable and sustainable dimensions within the complex public transportation sector.